2005
DOI: 10.1093/jurban/jti055
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of HIV Infection Among Incarcerated Women: Implications for Improving Detection of HIV Infection

Abstract: The prevalence of HIV infection in correctional settings is several-fold higher than found in community settings. New approaches to identifying HIV infection among

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 35 publications
2
45
0
6
Order By: Relevance
“…[1][2][3] For example, evaluation of a large number of incarcerated adults revealed that leukopenia correlated strongly with HIV seropositivity, independent of other variables, such as sex with an HIV-positive (HIV ϩ ) partner, injection drug use, ethnicity, and presence of sexually transmitted diseases. 4,5 Interestingly, in these studies, the risk for HIV seropositivity associated with leukopenia and a history of sex with an HIV ϩ partner were similarly high, 4 underscoring that leukopenia is strongly associated with HIV positivity in at-risk persons and is commonly observed soon after HIV infection. Of note, although the sine qua non feature of infection with HIV is progressive immunodeficiency related to CD4 ϩ T-cell lymphopenia, 6 CD4 ϩ T-cell counts contribute minimally in quantitative terms to the overall white blood cell (WBC) count and their decline during the course HIV infection contributes minimally to this observed leukopenia, which is mainly attributable to neutropenia.…”
Section: Introductionmentioning
confidence: 87%
“…[1][2][3] For example, evaluation of a large number of incarcerated adults revealed that leukopenia correlated strongly with HIV seropositivity, independent of other variables, such as sex with an HIV-positive (HIV ϩ ) partner, injection drug use, ethnicity, and presence of sexually transmitted diseases. 4,5 Interestingly, in these studies, the risk for HIV seropositivity associated with leukopenia and a history of sex with an HIV ϩ partner were similarly high, 4 underscoring that leukopenia is strongly associated with HIV positivity in at-risk persons and is commonly observed soon after HIV infection. Of note, although the sine qua non feature of infection with HIV is progressive immunodeficiency related to CD4 ϩ T-cell lymphopenia, 6 CD4 ϩ T-cell counts contribute minimally in quantitative terms to the overall white blood cell (WBC) count and their decline during the course HIV infection contributes minimally to this observed leukopenia, which is mainly attributable to neutropenia.…”
Section: Introductionmentioning
confidence: 87%
“…A prisão é, então, considerada um lugar de alto risco, principalmente pela heterogeneidade da população confinada no mesmo espaço tais como assassinos, traficantes, trabalhadores do sexo, indivíduos vivendo regras próprias, tendo como conseqüência maior exposição a riscos físicos, psicológicos, transmissão de doenças infecciosas que tanto podem ser trazidas para dentro da prisão como serem adquiridas dentro dela 3,9,10 . O confinamento estimula práticas que aumentam o risco de transmissão de doenças infecciosas tanto pelos comportamentos sexuais inadequados como pelo uso de drogas 9,11 .…”
Section: Introductionunclassified
“…O confinamento estimula práticas que aumentam o risco de transmissão de doenças infecciosas tanto pelos comportamentos sexuais inadequados como pelo uso de drogas 9,11 . Um número grande de estudos evidencia o papel do uso de drogas, principalmente as injetáveis, como responsável pela transmissão do HIV dentro das prisões 4,7,8,10 e que, por analogia na forma de transmissão, poderíamos atribuir a esses mesmos componentes um papel semelhante para a transmissão do HCV.…”
Section: Introductionunclassified
“…Nonetheless, few studies in the literature have examined female prisoners' sexual profile, their health problems, and the prevention strategies used in Brazilian prisons, particularly in regard to sexually transmitted diseases or infection with the human immunodeficiency virus (STD/HIV) (8) . It is worth emphasizing that prisons represent a high-risk environment because the heterogeneity of the incarcerated population results in high exposure to physical and psychological risks and to infectious diseases (9) . In addition, the biological characteristics of women make them particularly susceptible to STD/ HIV compared with the male prison population (3) .…”
Section: Introductionmentioning
confidence: 99%